HUBUNGAN ETOS KERJA TERHADAP KESEJAHTERAAN PETANI KARET DI DESA PULAU PULAU MUNGKUR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Marias, Pendi; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the Effect of Work Ethic on the Welfare of Rubber Farmers in Pulau Mungkur Village, Gunung Toar District, Kuantan Singingi Regency. This type of research is quantitative usingcorrelation Pearson product moment . Data collection techniques used were quizzes and direct observation sheets. The analysis used is quantitative analysis which is presented in the form of a table and then given an explanation. The result of this study is that there is a correlation between Work Ethics on the Welfare of Rubber Farmers in Pulau Mungkur Village, Gunung Toar District, Kuantan Singingi Regency. Based on the results of this study the work ethic influences the welfare of rubber farmers in Pulau Mungkur Village, Gunung Toar District, Kuantan Singingi Regency.Keywords: Work Ethics, welfare of farmers